Mathematical Model for Mapping Students’ Cognitive Capability - Hardi Tambunan (Institute of Advanced Engineering and Science, 2016)
The quality mapping of educational unit program is important issue in education in Indonesia today in an effort to improve the quality of education. The objective of this study is to make a mathematical model to find out the map of students’ capability in mathematics. It has been made a mathematical model to be used in the mapping of students’ capability. Demonstration of the use of models performed in accordance with the data of the results from the math test given to 147 students in grade XII, state senior high school, science program, and academic year 2015-2016. The map of students’ capability can be known that 48 test items are derived from 16 sub topics of three cognitive domain, only 19 test items are achieved. The achieved map lies in 8 sub topics for knowledge domain and 6 sub topics for comprehension domain and application domain has 5 sub topics. So that sub topic and cognitive domain which can not be achieved can be done further corrective action to obtain the maximum results. This paper demonstrates how operational research techniques can be applied for problem solving in education.